2017
DOI: 10.1111/bph.13753
|View full text |Cite
|
Sign up to set email alerts
|

Metformin attenuates angiotensin II‐induced TGFβ1 expression by targeting hepatocyte nuclear factor‐4‐α

Abstract: This article is part of a themed section on Spotlight on Small Molecules in Cardiovascular Diseases. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.8/issuetoc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Metformin is also an insulin sensitizer and may play a protective role in the intestinal lumen through a variety of mechanisms (Flory and Lipska, 2019;Horakova et al, 2019). Metformin can also reduce low density lipoprotein cholesterol (LDL-C) and total cholesterol (TC) levels (Xu et al, 2015;Weng et al, 2020); inhibit inflammatory responses (such as inhibiting the activation of nuclear factor kappa B [NF-kB] and interleukin-1b ) (Isoda et al, 2006;Deng et al, 2018); improve vascular endothelial function (activate 5'-adenosine monophosphateactivated protein kinase [AMPK], increase nitric oxide [NO] synthesis) (Nafisa et al, 2018;Sardu et al, 2019); inhibit cardiac remodeling (such as inhibiting cardiomyocytes apoptosis and cardiac fibrosis) (Sasaki et al, 2009;Chen R. et al, 2018). These suggest that metformin has a cardiovascular protective effect, but a comprehensive understanding of the mechanism of action of metformin is still lacking (Rena et al, 2017;Flory and Lipska, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Metformin is also an insulin sensitizer and may play a protective role in the intestinal lumen through a variety of mechanisms (Flory and Lipska, 2019;Horakova et al, 2019). Metformin can also reduce low density lipoprotein cholesterol (LDL-C) and total cholesterol (TC) levels (Xu et al, 2015;Weng et al, 2020); inhibit inflammatory responses (such as inhibiting the activation of nuclear factor kappa B [NF-kB] and interleukin-1b ) (Isoda et al, 2006;Deng et al, 2018); improve vascular endothelial function (activate 5'-adenosine monophosphateactivated protein kinase [AMPK], increase nitric oxide [NO] synthesis) (Nafisa et al, 2018;Sardu et al, 2019); inhibit cardiac remodeling (such as inhibiting cardiomyocytes apoptosis and cardiac fibrosis) (Sasaki et al, 2009;Chen R. et al, 2018). These suggest that metformin has a cardiovascular protective effect, but a comprehensive understanding of the mechanism of action of metformin is still lacking (Rena et al, 2017;Flory and Lipska, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The United Kingdom Prospective Diabetes Study (UKPDS) indicated that metformin had cardiovascular protective effects beyond reducing blood glucose levels (Ovalle, 2009;Rojas and Gomes, 2013;Natali et al, 2019). By further detecting AMPK activation, it was found that metformin could markedly decrease transforming growth factor-b1 production by inhibiting HNF4a, and ultimately suppressed cardiac fibrosis (Chen et al, 2018). Moreover, the positive effects of metformin have been indicated in the treatment of a prolonged QT interval in a diabetic state.…”
Section: Introductionmentioning
confidence: 99%
“…These data mining findings suggest that APQ4 may not directly impact the transcription of TGFB1. On another hand, according still to the MEM database and webtool, AQP4 tightly co-expresses with angiotensinogen (AGT) (p-value: 2.95 −41 , Pearson correlation test), a gene upregulated in MS spinal cords [11] and extensively shown to promote the TGFB1 pathway [26][27][28][29]. Similarly in mice, Aqp4 tightly co-expresses with Agt (p-value: 5.85 −21 , Pearson correlation test).…”
mentioning
confidence: 99%
“…Similarly in mice, Aqp4 tightly co-expresses with Agt (p-value: 5.85 −21 , Pearson correlation test). Of note, Angiotensin II, the main active metabolite of angiotensinogen, not only stimulates the transcription of TGFB1 [26,29] but exerts short-term activating effects on SMADs [30][31][32], the transducing molecules of the TGF-beta pathway. Along this line, under conditions of acute neuronal insult, the engagement of the angiotensin II receptor type 1 on murine astrocytes is mandatory to contain the influx of blood leucocytes through the blood brain barrier [33].…”
mentioning
confidence: 99%